Determinants of Virologic Failure among Adult HIV Patients on First-Line Antiretroviral Therapy at Waghimra Zone, Northern Ethiopia: A Case-Control Study - Abrham Emagnu; Zenahebezu Abay; Abera Balcha Bulti; Yaregal Animut (Advances in Public Health)
Introduction. The primary goal of antiretroviral therapy (ART) is to reduce the viral load in HIV-infected patients to promote quality of life, as well as to reduce HIV-related morbidity and mortality. A high rate of virologic failure was reported in Waghimra Zone, Northwest Ethiopia, in viral load assessment conducted among HIV-infected patients on ART in the Amhara region. However, there is limited evidence on the determinants of virological failure in the study area. This study aimed to identify the determinants of virological failure among HIV-infected patients on antiretroviral therapy in Waghimra zone, Northern Ethiopia, 2019. Methods. An institutional-based unmatched case-control study was conducted from May 21 to June 30, 2019. Cases were people living with HIV (PLHIV) on ART who had already experienced virological failure; controls were those without virological failure. Data were extracted from 92 cases and 184 controls through chart review using a pretested and structured checklist. The data were entered using Epi Info version 7 and exported to SPSS version 20 for analysis. A multivariate logistic regression analysis was carried out to identify factors associated with virological failure, and variables with a P value <0.05 were considered statistically significant. Results. This study revealed that poor adherence to ART (adjusted odds ratio (AOR) = 4.24, 95% confidence interval (CI): 2.17, 8.31), taking ART for longer than five years (AOR = 3.11, 95% CI: 1.17, 8.25), having drug toxicity (AOR = 3.34, 95% CI: 1.54, 7.23), age of PLHIV ≥ 35 years (AOR = 2.45, 95% CI: 1.29,4.64), and recent CD4 count <200 cells/mm³ (AOR = 3.06, 95% CI: 1.52, 6.13) were factors associated with virologic failure. Conclusion and Recommendation. This study showed that poor adherence to treatment, longer duration on ART, experiencing drug toxicity, older age, and recent CD4 <200 cell/mm³ are factors that increase the risk of virologic failure.